Performance of doctors and nurses in emergency care for hemophiliac patients - Stefane Vieira Nobre, José Adelmo da Silva Filho, Natália Bastos Ferreira Tavares, Luan Rodrigues Teixeira, Antonio Germane Alves Pinto (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/reufpi.v9i0.11056